Englisch past and perfeft as semantically vacuous mood markers - Schulz, Katrin (Proceedings of the Amsterdam Colloquium, 2007)
This paper presents an explanation for the observation that in some contexts the English simple past appears not to be interpreted as semantic past tense. We will propose (i) that English sentences obligatorily carry mood, (ii) that the English simple past is lexically ambiguous between expressing tense or mood, and (iii) that the semantic function of mood is to facilitate modal subordination.